Respons inflamasi pada pulpa gigi tikus setelah aplikasi ekstrak etanol propolis (EEP) (The inflammatory response on rat dental pulp following ethanolic extract of propolis (EEP) application) - Ardo Sabir (Dental Journal (Majalah Kedokteran Gigi), 2005)
Propolis is a resinous hive product collected by bees from tree buds and mixed with secreted bee wax in order to avoid bacterial contamination in the hive, and also to seal it. Propolis is employed for the treatment of various infectious diseases because it is wellknown that is has antibacterial and anti-inflammatory properties. The therapeutic use of propolis in dentistry has been done in recent years as in treatment gingivitis and dental caries, in treatment wound healing after surgical procedures, etc. The purpose of this investigation was to study the inflammatory response on rat's dental pulp following application of ethanol extract of propolis (EEP). Twelve male Spraque-Dawley rats of 8–16 week old and 200–250 grams in weight were used in this study. The rats were randomly divided into two groups. Pulp exposures were performed on the occlusal surface of right maxillary first molars. At the first group, as the control group, zinc oxide-based filler was directly applied on pulp exposure. Meanwhile at the second group, as the sample group, pulp exposure was applied with EEP. After that, all cavities were filled with glass ionomer cement as permanent filling. Animals were sacrificed on the 7th, 14th, and 28th day. The criterion of histological examination was based on the inflammatory responses of the dental pulp, which were the presence of polymorph nuclear leukocytes and macrophages. Kruskall-Wallis and Mann-Whitney tests were employed to analyze the data. The results of this research demonstrated that the inflammatory response of EEP group was numerically milder compared to the control group, even though statistical analysis showed no significant difference (p > 0.05) between the two groups.